TVET as a Leadership Incubator: Preparing an Adaptive Generation for the Future Economy - Avela Ngqunguza; Thami Issac Makhoba (Universitas Nurul Jadid, 2025)
This study examines the urgency of Vocational Education and Training (TVET) universities in equipping students with essential leadership skills to face the dynamics of the changing global job market. Although the role of TVET is crucial, there are gaps in the literature regarding how these institutions specifically foster leadership and align it with economic demands. Through a qualitative approach with a case study design, this study examines the educational strategies employed in TVET institutions in South Africa, drawing on the perspectives of both students and lecturers. The findings indicate that leadership training programs are generally received positively, particularly in enhancing communication skills, decision-making, and teamwork through experiential learning methods, such as collaborative projects and internships. Nonetheless, interpersonal challenges and variations in student readiness levels are still a concern. Lecturers confirmed the high value of hands-on experience and recommended integrating leadership modules early in the curriculum, as well as utilizing simulation technology to enhance learning outcomes. This research provides profound implications on effective practices, fills empirical gaps, and contributes to the understanding of TVET's role in shaping adaptive leaders who are ready to face the economic complexities of the future.